The power of giving away power : how the best leaders learn to let go - Barzun, Matthew Winthrop, 1970- (Optimism Press, an imprint of Penguin Random House LLC, 2021)
"How do great leaders thrive in uncertain times? By changing their mindsets about power. Why do some organizations grow and thrive with complexity, while others collapse under their own weight? The answer is simple, but transformative: When power is hoarded and lorded over others, it is finite. But when leaders allow power to flow among groups, it can grow indefinitely. While many have realized the limits of top-down hierarchy, "bottom-up" leadership is just as bad. It's the same shape in reverse. And who wants to be at the bottom? Barzun describes leaders whose organizations take a new shape. They are self-perpetuating and self-energizing; they function as Constellations-- dynamic, flexible, and renewable networks of distinct yet interwoven nodes. Barzun shows us how we can distribute power throughout an organization by using friction in decision-making, seeing more clearly when growth is being stifled, and fostering creativity and innovation in every part of the organization. In The Power of Giving Away Power, Barzun brilliantly layers lessons from American history and business with insights from his career in tech, politics, and diplomacy to show how we can lead meaningful change in our companies, communities, and even our nations by adopting this mindset. Through profiles of leaders as varied as Jane Jacobs, Dee Hock of Visa, and President Obama, Barzun shows how we can all create Constellations. As Barzun writes, change starts with recognizing "the power we can create by seeing the power in others"--and making the leap to lead, together"--